2017
DOI: 10.1002/jssc.201700334
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of amino acids using serially coupled columns

Abstract: Single conventional columns in reversed-phase liquid chromatography are insufficient for analysing the isoindoles of primary amino acids due to their limited functionality. An interesting possibility for increasing the separation power is the combination of several columns of different nature, where the length is modified by coupling small segments. This approach may require a considerable investment to have multiple lengths for each stationary phase. However, the combination of only two columns of fixed lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Such high S LSS values are one of the reasons why gradient elution is indispensable in RPLC of proteins. Selectivity could be improved by serially coupling columns with increasing retentive capacity and applying multistep gradients [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…Such high S LSS values are one of the reasons why gradient elution is indispensable in RPLC of proteins. Selectivity could be improved by serially coupling columns with increasing retentive capacity and applying multistep gradients [49,50].…”
Section: Methodsmentioning
confidence: 99%
“…Previous works have demonstrated the improved efficiency and selectivity when columns are connected in series. 23,26,28,29 The increased length translates into higher peak capacity, especially when more columns packed with the same stationary phase are serially installed. 30−32 different stationary-phase columns.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that serially connected columns can outperform the same columns used separately, suggesting that this tandem column approach has a unique advantage to improve selectivity. 21,23,26,28,31,33,34 Welch and co-workers reported the use of tandem supercritical fluid chromatography (SFC) screening, which facilitates identification of column and modifier combinations for separation of small-molecule mixtures. 34 A challenege associated with tandem column separation is to select ideal method parameters such as pH, temperature, eluent composition, and gradient programs as they all need to be compatible for all the column combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has been involved since 2012 in the improvement of separations in RPLC using serially coupled (tandem) columns [8,[11][12][13][14][15]. The successful development of such column systems required solving technical problems related to the robustness of connections, reduction of extra dead volumes, or deterioration of column packings.…”
Section: Introductionmentioning
confidence: 99%
“…Tandem columns are powerful, but they may require considerable investment, since multiple columns of different lengths are needed for each stationary phase. Recently, we have demonstrated that the combination of only two columns of fixed length may be enough to resolve relatively complex samples satisfactorily, provided that an optimized gradient program is applied . It should be also considered that the search of the best separation conditions requires modeling the chromatographic behavior of two or more stationary phases, although there is no need to develop models for each column length, since these can be derived from the models obtained for a column with a specific length taken as reference .…”
Section: Introductionmentioning
confidence: 99%